Participatory evaluation as an instrument of popular education - Jeff Zacharakis-Jutz (Adult Education Research Conference, 1994)
In 1991, Lindeman Center staff began working with ten United Way agencies in the Rockford, Illinois, area to develop an evaluative approach that enhanced their capacity for self-directed decision making. Through a collaborative process, the participating agencies decided to experiment with the participatory evaluation approach. This paper discusses this project within the framework of North American of popular education.